Body mass index and associated lifestyle and eating behaviours of female students at a South African university - (:unkn) unknown (My University, 2017)
Objective: To determine the prevalence of obesity and the physical activity, sitting time, and eating behaviours associated with BMI in a group of undergraduate female students at a South African university.Methods: A cross-sectional study of 110 female undergraduate students, registered at the University of the Witwatersrand, Johannesburg. Validated self-reported questionnaires were used for physical activity and eating behaviours; and body mass index (BMI) was collected using standardised methods.Results: The presence of obesity in the sample was 17.3%, with a mean BMI of 25.4 ± 4.63 kg/m2. Those with BMIs ≥ 25 kg/m2 were less likely to be physically active and purchase fruits than those with normal BMIs. Close proximity to food vendors (≤500m) (β: 0.25), peer influence (β: 0.26), sitting time (β: 0.20) and purchasing fried foods ≥ 4 times/week (β: 0.87) were positively associated with BMI (all p < 0.05).Conclusion: Given the period of susceptibility and potential for shaping healthy behaviour, public health initiatives addressing obesity should target the high sitting times of students and eating behaviour, particularly during the period of transition from adolescence to adulthood.
Keywords: African Research